2021
DOI: 10.3390/polym13183088
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization Shrinkage of Short Fiber Reinforced Dental Composite Using a Confocal Laser Analysis

Abstract: The purpose of this study was to investigate the polymerization shrinkage of short fiber reinforced composite (SFRC) using a multicolor confocal displacement laser that can measure the polymerization shrinkage with high accuracy. The three types of SFRCs used in this study were XD (Ever X Flow Dentin), XB (Ever X Flow Bulk), and XP (EverX Posterior). In addition, CF (Clearfil majesty ES Flow) with hybrid type filler was used as a control. The measured values of the final polymerization shrinkage rate and amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The superior results of SFRC might be attributed to its unique structure with short glass fibers of 0.3-1.9 mm embedded in the resin matrix [44]. As the fibers are randomly oriented in the material, they might be able to control the shrinkage and the resulting stress on the cavity walls as the material is not able to shrink in the direction of the fibers, only perpendicular to them [30,45]. In contrary, Fronza et al demonstrated higher shrinkage stress values of SFRC samples and their result was explained by high inorganic content and resultant high elastic modulus of the material [18].…”
Section: Discussionmentioning
confidence: 99%
“…The superior results of SFRC might be attributed to its unique structure with short glass fibers of 0.3-1.9 mm embedded in the resin matrix [44]. As the fibers are randomly oriented in the material, they might be able to control the shrinkage and the resulting stress on the cavity walls as the material is not able to shrink in the direction of the fibers, only perpendicular to them [30,45]. In contrary, Fronza et al demonstrated higher shrinkage stress values of SFRC samples and their result was explained by high inorganic content and resultant high elastic modulus of the material [18].…”
Section: Discussionmentioning
confidence: 99%